Bigel-based low-fat sponge cake production for palm oil replacement - Yilmaz, Ezgi Genc; Akcicek, Alican; Cimen, Sumeyra; Karasu, Salih; Boga, Tugce; Tekin-Cakmak, Zeynep Hazal; Dertli, Enes (SPRINGER, 2026)
The development of healthier and sustainable fat replacers in bakery products has become a priority due to health concerns and environmental issues associated with palm oil. To the best of our knowledge, this is the first work to demonstrate the synergistic functionality of soy wax, beeswax, and citrus fiber in a bigel system intended for fat replacement in bakery products. In this study, food-grade bigels were formulated by combining oleogels structured with soy wax and beeswax (3%, 5%, 7%, and 10%) with 5% citrus fiber hydrogels at two phase ratios (40:60 and 60:40, oleogel:hydrogel). The rheological, textural, thermal, microstructural, and centrifugal stability properties of these bigels were systematically characterized and compared with palm oil. Rheological analyses revealed that all bigels exhibited solid-like behavior (G' > G''), with (10BW OG)60-HG40 showing the highest mechanical strength and thermal stability up to 60 degrees C. Thixotropy tests demonstrated excellent structural recovery in (10BW OG)60-HG40, making it suitable for high-shear processes like batter mixing. Texture profile analysis showed that (10BW OG)60-HG40 and (10BW OG)40-HG60 had the highest hardness among gels, yet (10BW OG)60-HG40 yielded the softest sponge cake, indicating improved aeration and moisture retention. Color analysis indicated brighter crumb and crust in bigel-incorporated cakes, attributed to the high water content and reduced Maillard browning. Microscopy revealed that the highest wax-containing bigels formed dense crystalline networks, correlating with superior rheological and stability characteristics. Among all formulations, (10BW OG)60-HG40 and (3SW:7BW OG)40-HG60 stood out as the most promising palm oil replacers, offering a balance between structural integrity and thermal resistance. This study provides a novel fat replacement strategy by combining soy wax, beeswax, and citrus fiber, and demonstrates its practical functionality in low-fat sponge cake applications.
Keywords: Beeswax; Bigel; Citrus fiber; Oleogel; Palm oil replacer; Soy wax; WAX; Food Science & Technology